Geographical issues on maritime names : special reference to the East Sea. - Tongbuga Yoksa Chaedan (Korea) (Seoul, Korea : Northeast Asian History Foundation, 2010)
This book contains seventeen papers selected from seminars of The International Seminar on Sea Names presented annually since 1995. They range in focus from discussing the principles and practices of naming seas and accompanying issues of international standardization and documentation to research on finding a resolution to the chronic disputes between Korea and Japan on the name of the sea between them.
Includes bibliographical references and index.
Keywords: Toponymy -- Political aspects; Names, Geographical -- Political aspects; Political geography; Territorial waters; Names, Geographical -- Japan, Sea of; Japan, Sea of -- Names